Somapacitan, a once‐weekly reversible albumin‐binding GH derivative, in children with GH deficiency: A randomized dose‐escalation trial. (8th August 2017) - Battelino, Tadej; Rasmussen, Michael Højby; De Schepper, Jean; Zuckerman‐Levin, Nehama; Gucev, Zoran; Sävendahl, Lars; ,
Summary: Objective: To evaluate the safety, local tolerability, pharmacodynamics and pharmacokinetics of escalating single doses of once‐weekly somapacitan, a reversible, albumin‐binding GH derivative, vs once‐daily GH in children with GH deficiency (GHD). Design: Phase 1, randomized, open‐label, active‐controlled, dose‐escalation trial (NCT01973244). Patients: Thirty‐two prepubertal GH‐treated children with GHD were sequentially randomized 3:1 within each of four cohorts to a single dose of somapacitan (0.02, 0.04, 0.08 and 0.16 mg/kg; n=6 each), or once‐daily Norditropin ® SimpleXx ® (0.03 mg/kg; n=2 each) for 7 days. Measurements: Pharmacokinetic and pharmacodynamic profiles were assessed. Results: Adverse events were all mild, and there were no apparent treatment‐dependent patterns in type or frequency. Four mild transient injection site reactions were reported in three of 24 children treated with somapacitan. No antisomapacitan/anti‐human growth hormone (hGH) antibodies were detected. Mean serum concentrations of somapacitan increased in a dose‐dependent but nonlinear manner: maximum concentration ranged from 21.8 ng/mL (0.02 mg/kg dose) to 458.4 ng/mL (0.16 mg/kg dose). IGF‐I and IGFBP‐3, and change from baseline in IGF‐I standard deviation score (SDS) and IGFBP‐3 SDS, increased dose dependently; greatest changes in SDS values were seen for 0.16 mg/kg. IGF‐I SDS values were between −2 and +2 SDS, except for peak IGF‐I SDS with 0.08 mg/kg somapacitan. Postdosing, IGF‐I SDS remained above baseline levels for at least 1 week. Conclusions: Single doses of once‐weekly somapacitan (0.02‐0.16 mg/kg) were well tolerated in children with GHD, with IGF‐I profiles supporting a once‐weekly treatment profile. No clinically significant safety/tolerability signals or immunogenicity concerns were identified.